Das Gold des Himalaja - Nomadenleben in Ladakh . Gold of the Himalayas - The Nomad Life in Ladakh - Wartmann, Thomas (Filmquadrat, 2007)
Verzio FF Submission The Changpa nomads live cut off from the rest of the world on a barren plateau at an altitude of 4000 meters in the southeast of Ladakh, the mountain region in Kashmir annexed by India. The film tells the story of the nineteen-year-old nomad son Norbu, who has kidnapped his bride, the young Tashi, from Leh, the capital city of Ladakh. Wife stealing is nothing unusual for the Changpa, but custom does demand that an apology be made to the father of the bride. Norbu is supposed to take over his father’s tent and learn the nomadic trade but the boy, who grew up in the city, cannot reintegrate himself into the grueling daily life of the mountain nomads. The young couple cannot endure these conditions. By the time he sets off with his father to Leh to apologize to his father in law, his decision has been made: he will turn his back on the nomadic life and become a truck driver in the valley.